ASSESSMENT OF FINANCIAL PERFORMANCE OF FOOD AND BEVERAGE COMPANIES IN INDONESIA WITH THE DUPONT SYSTEM METHOD - Dyah Shinta Kusumaningtyas; Salsa Ika Fitriyani; Joelianti Dwi Supraptiningsih (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This study aims to evaluate the financial performance of companies in the food and beverage subsector in Indonesia. A descriptive method integrated with a quantitative approach is utilized in this study to systematically analyze the research data. This system decomposes Return on Equity (ROE) into three key components: Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM). The analysis is based on financial data from nine food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. These companies include PT Indofood Sukses Makmur, PT Mayora Indah, PT Cisarua Mountain Dairy, PT Ultra Jaya Milk, PT Garudafood, PT Siantar Top, PT Campina Ice Cream, PT Sariguna Primatirta, and PT Akasha Wira International.The findings indicate that the overall financial performance of these companies is relatively stable and healthy. However, the efficiency of asset utilization remains suboptimal and requires improvement to enhance overall performance. The study recommends a greater focus on operational efficiency, particularly in managing both fixed and current assets. Furthermore, the results suggest that investors should consider not only the overall ROE but also its individual components when making investment decisions.